2015
DOI: 10.1097/mib.0000000000000483
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric IBD-unclassified Is Less Common than Previously Reported; Results of an 8-Year Audit of the EUROKIDS Registry

Abstract: Only half of patients reported as IBD-U in EUROKIDS had undergone complete diagnostic workup. Follow-up with reinvestigations resulted in a reduction of IBD-U rate to 5.6%. A diagnosis of IBD-U becomes less likely in case of complete diagnostic workup. Implementation of clear diagnostic criteria will further reduce the rate of IBD-U in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 26 publications
4
39
0
Order By: Relevance
“…By our new 'prevalent' IBD subtype definition, the prevalence of pediatric IBD-U was 18%, which is still higher than in adults, and higher than reported in a large European cohort study at end of follow-up: 5.6% [32]. The distinction between CD and UC can at times be more challenging in pediatric populations since colonic CD is a more common [60].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…By our new 'prevalent' IBD subtype definition, the prevalence of pediatric IBD-U was 18%, which is still higher than in adults, and higher than reported in a large European cohort study at end of follow-up: 5.6% [32]. The distinction between CD and UC can at times be more challenging in pediatric populations since colonic CD is a more common [60].…”
Section: Discussionmentioning
confidence: 67%
“…In other studies, 23-84% of patients with an initial diagnosis of IBD-U were later classified as UC or CD [9,12,24,[31][32][33]55]. In pediatric patients, a systematic review found an increase in diagnosis of CD over time, and a decrease in IBD-U [7].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…UC and IBD-unclassified (IBD-U) account for 30-40 percent of pediatric IBD in the United States and Europe. 5-7 Furthermore, approximately 80 percent of children with CD have colonic involvement with 25 percent exhibiting a colon-only phenotype with no small intestinal involvement. 8,9 Colon-only CD phenotype is even more common with younger age, occurring in about 40 percent of children under 10 years of age.…”
mentioning
confidence: 99%
“…Increasing prevalence and hospitalization rates have been reported [1][2][3]. Early diagnosis and monitoring of disease are important to prevent progression, but complicated by highly variable disease manifestations, which may not only affect the gastrointestinal tract but also the skin and eyes [4][5][6]. Therefore, there is a great need for reliable biomarkers for early diagnosis and disease monitoring [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%